Analisis Perhitungan dan Pengendalian Mutu Pekerjaan Beton Pada Pembangunan Gedung PD Panca Karya Ambon (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2023)
Engineering and quality control of concrete work is carried out to measure and monitor variations in the composition of the mixture as well as measure and monitor work activities that will affect the strength and homogeneity of concrete as well as the construction of privately owned buildings such as the PD Panca Karya Ambon Building must also meet predetermined requirements the. The operational work in question is batching, mixing, placing, curing, and testing. The need to monitor concrete quality is not only to ensure concrete meets technical standards but also for economic reasons. If a low level of control is exercised, it will result in a higher standard deviation, so a higher average strength must be achieved, which of course requires more cement. Supervision of concrete work must be carried out at all stages of work from the initial work to the final work in the form of mixed tests.